Удосконалення нормативно-правового регулювання діяльності закладів вищої освіти МВС України, які готують поліцейських - Бугайчук, К. Л.; Buhaichuk, K. L.; Костянтин Бугайчук (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2022. – № 3. – С. 283-292, 2022)
У статті проаналізовано останні нормативні зміни до законодавства України про вищу освіту в частині удосконалення діяльності закладів вищої освіти із специфічними умовами навчання. Проведений порівняльно-правовий аналіз повноважень закладів вищої освіти із специфічними умовами навчання щодо розробки власних нормативних актів, інструкцій, вимог щодо організації освітнього процесу. На підставі проведеного дослідження сформульовано пропозиції щодо удосконалення змісту нормативно-правових актів, що стосуються організації освітнього процесу у закладах вищої освіти із специфічними умовами навчання, порядку підготовки здобувачів наукового ступеня «доктор філософії» та «доктор наук», порядку призначення керівників цих закладів та вимоги до осіб, що претендують на посади ректорів закладів вищої освіти із специфічними умовами навчання.

The article analyzes the latest regulatory changes to the legislation of Ukraine on higher education in terms of improving the activities of higher education institutions with specific study conditions. A comparative and legal analysis of the powers of higher education institutions with specific learning conditions regarding the development of their own normative acts, instructions, requirements for the organization of the educational process, as well as the procedure for appointing the heads of these higher education institutions was carried out. On the basis of the conducted research, it was concluded that the changes that were made to the legislation on higher education in the part of the organization of military education do not fully correspond to the provisions of the Law of Ukraine «On Higher Education», giving rise to internal competition of the norms of this law, which, in turn, has a negative impact on the autonomous rights of such institutions regarding the organization of the educational process, the determination of Also, the Ministry of Education and Science has been granted broad discretionary powers to control the regulatory support of the activities of higher education institutions with specific learning conditions, which, firstly, violate the principles of the activities of central executive bodies, and, secondly, threaten the autonomy of higher education institutions with specific learning conditions. It has been proven that the departmental regulatory framework for the activities of higher education institutions of the Ministry of Internal Affairs system that train police officers needs to be significantly updated and brought into line with modern requirements. In particular, there is a need to improve the departmental procedure for the training of higher education applicants for the degrees of Doctor of Philosophy and Doctor of Science in research institutions that belong to the sphere of administration of the Ministry of Internal Affairs of Ukraine. The procedure for appointing rectors (heads) of higher education institutions with specific conditions also needs further regulation education, by developing and amending the Law of Ukraine «On Higher Education», as well as approval of requirements and criteria for such persons by the Government of Ukraine and the Ministry of Internal Affairs of Ukraine.

В статье проанализированы последние нормативные изменения в законодательство Украины о высшем образовании в части усовершенствования деятельности высшего образования со специфическими условиями обучения. Проведен сравнительно-правовой анализ полномочий высшего образования со специфическими условиями обучения по разработке собственных нормативных актов, инструкций, требований по организации образовательного процесса. На основании проведенного исследования сформулированы предложения по усовершенствованию содержания нормативно-правовых актов, касающихся организации образовательного процесса в учреждениях высшего образования со специфическими условиями обучения, порядка подготовки соискателей научной степени «доктор философии» и «доктор наук», порядка назначения руководителей этих заведений и требования к лицам, которые претендуют на должности ректоров высшего образования со специфическими условиями обучения.
Improvement of regulatory and legal regulation of the activities of higher education institutions of the MIA of Ukraine which train police officers
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; МВС України; вища освіта; заклади вищої освіти зі специфічними умовами навчання; освітній процес; наукова діяльність; Ministry of Internal Affairs of Ukraine; higher education; establishments of higher education with the specifc terms of studies; educational process; scientific activity; МВД Украины; учреждения высшего образования со специфическими условиями обучения; образовательный процесс; научная деятельность